Knowledge for environmental governance: probing science–policy theory in the cases of eutrophication and fisheries in the Baltic Sea. Issue 6 (2nd November 2017) - Saunders, Fred P.; Gilek, Michael; Linke, Sebastian
ABSTRACT: How science and policy interact has been a major research focus in the International Relations (IR) tradition, using the epistemic community (EC) concept, as well as in the alternative perspective of Science and Technology Studies (STS). Should science be autonomous and as apolitical as possible in order to 'speak truth to power', as suggested by EC or should the inevitable entanglement of science and politics be accepted and embraced so as to make advice more conducive to negotiating the explicit travails of political decision-making as suggested by STS? With this point of departure, we compare similarities and differences between science–policy interactions in the issue areas of eutrophication and fisheries management of the Baltic Sea. To examine how knowledge is mobilised, the concepts of 'uncertainty' and 'coherence' are developed, drawing on both EC and STS thinking. We then reflect on the explanatory value of these approaches in both cases and discuss how a separation of science and policy-making in the pursuit of achieving scientific consensus leads to ineffectual policies. Drawing on STS thinking, we urge for a re-conceptualisation of coherence in order to accommodate a more reflexive practice of science–policy interactions.